The Effect of Teacher's Social Competence on Increasing Human Resources at SMP Muhammadiyah 9 Tanggulangin Boarding School - Febbianti Widia Santoso; Nurdyansyah Nurdyansyah; Taufiq Churrahman (Proceedings of The ICECRS, 2020)
The result of observations of social competence of teachers in SMP Muhammadiyah 9 Tanggulangin Boarding School is the rise of news that social competence of teachers is very influential on the development of each institution, here the author wants to know how social competencies possessed by teachers at SMP Muhammmadiyah 9 Tanggulangin Boarding School because schools This is an institution that is still relatively new and is still in the process of development. This is the background of this research. These problems are discussed through qualitative research conducted with the Grounded Research model. The subjects of this study were 25 teachers in SMP Muhammadiyah 9 BS Tanggulangin. The object of this study is the influence of teacher social competence on improving human resources at SMP Muhammadiyah 9 Tanggulangin Boarding School. Data collection techniques in this study used tests, observations, interviews and documentation. From the results of the study, showed that the social competence of teachers in SMP Muhammadiyah 9 Tanggulangin Boarding School has a pretty good value based on the results of the test of the teacher's social competency instrument which shows the value of each description is 4 with a total score of 100, and from the interviews it can be concluded that there is an influence which is significant from the social competence of teachers to increase human resources in SMP Muhammadiyah 9 Tanggulangin Boarding School with a focus on increasing the number of students and increasing teaching staff in the last 5 years since the foundation of this institution.